Drosophila as a Model Organism in Host–Pathogen Interaction Studies - Younes, Salma; Al-Sulaiti, Asma; Nasser, Elham Abdulwahab Ahmed; Najjar, Hoda; Kamareddine, Layla (Frontiers in Cellular and Infection Microbiology, 2020)
Owing to the genetic similarities and conserved pathways between a fruit fly and mammals, the use of the Drosophila model as a platform to unveil novel mechanisms of infection and disease progression has been justified and widely instigated. Gaining proper insight into host-pathogen interactions and identifying chief factors involved in host defense and pathogen virulence in Drosophila serves as a foundation to establish novel strategies for infectious disease prevention and control in higher organisms, including humans.